Biologically oriented preparation technique: an alternative for rehabilitating teeth and implants - Mayorga-Mera, Minerva Mariel (2022)
Objective. We show all available scientifc evidence on the biologically oriented preparation technique (BOPT), including relevant, unknown and controversial aspects of the subject. Methods. This study focuses on the analysis and clinical cases reported with this technique in different dental areas, including thedifferences between digital and conventional protocols used to rehabilitate dental structures and their cementation. Results. Forty-seven scientifc articles were collected from digital databases by assessing the quality of the studies and established exclusion and inclusion criteria. BOPT has a stable periodontalprosthetic relationship; however, more  randomized studies are needed to support this dental preparation. Conclusions. The hours with the patient are increased and the experience of the clinician is fundamental, taking into accountthat digital methods speed up the process but increase the cost of the work.